The Implementation of Positive Discipline in Fostering Students' Responsibility - Rachmawati, Kembar; Roesminingsih, Erny; Kristanto, Andi (Al-Qalam Institue, 2025)
Character development and the cultivation of student responsibility are fundamental aspects of education. However, disciplinary practices in schools are still frequently implemented through punitive approaches that offer little opportunity for students to grow through self-awareness. This study aims to examine the implementation of positive discipline in fostering student responsibility at SMA Negeri 1 Kedamean and SMA Negeri 1 Manyar, two public senior high schools in Gresik Regency that have begun adopting more reflective and humanistic approaches to student development. This research employed a qualitative multi-site descriptive design. Data were collected through in-depth interviews, participatory observations, and document analysis. The findings reveal that the implementation of positive discipline through the restitution triangle model and the use of positive reinforcement strategies has effectively developed students’ intrinsic awareness and sense of responsibility. These approaches have shaped students’ adherence to school rules and improved their social relationships. The study also indicates that positive discipline can be applied flexibly in accordance with the specific cultural and contextual characteristics of each school, and it serves as a meaningful and educative alternative to punitive character education. The different approaches used by each school reflect their adaptation to their respective cultural environments. Based on the results, this study recommends the need for teacher training, parental engagement, and the development of school-wide policies rooted in non-punitive disciplinary frameworks.